A ticket to ride : a novel - McLain, Paula (Ecco, 2008)
Mesmerized by her older cousin Fawn, who has been sent to live with Jamie's family after a sex scandal involving a teacher, Jamie agrees to a makeover in order to win Fawn's approval but finds herself torn between her sexually awakened new self and the girl she used to be.